1998
DOI: 10.1063/1.122146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluorine on the diffusion of boron in ion implanted Si

Abstract: Ion implants of 1 keV B+11 and 5 keV BF2+, to a dose of 1×1015/cm2 at a tilt angle of 0°, were implanted into preamorphized (Si+,70 keV, 1×1015/cm2) wafers. These samples were rapid thermal annealed in an ambient of 33 ppm of oxygen in N2 at very short times (<0.1 s spike anneals) at 1000 and 1050 °C to investigate the effects of the fluorine in BF2 implants on transient enhanced diffusion (TED). By using a relatively deep preamorphization of 1450 Å, any difference in damage between the typically amorph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(44 citation statements)
references
References 4 publications
3
41
0
Order By: Relevance
“…3 Some authors suggested the modification of Si self-interstitial defect stability, 14 while others indicated that F did not have an effect on defect evolution. 15 In any case, a change in defect stability or the temporary trapping of Si I's would alter B diffusion during the transient period ͑while defects or complexes exist͒, but once defects had been completely annealed out and all Si I's were released, the overall B diffusion should correspond to the excess Si I's generated independently of the stability of defects or complexes where they may have been temporarily stored. 16 An additional contribution of F could be attributed to its transport capability of point defects.…”
Section: Resultsmentioning
confidence: 99%
“…3 Some authors suggested the modification of Si self-interstitial defect stability, 14 while others indicated that F did not have an effect on defect evolution. 15 In any case, a change in defect stability or the temporary trapping of Si I's would alter B diffusion during the transient period ͑while defects or complexes exist͒, but once defects had been completely annealed out and all Si I's were released, the overall B diffusion should correspond to the excess Si I's generated independently of the stability of defects or complexes where they may have been temporarily stored. 16 An additional contribution of F could be attributed to its transport capability of point defects.…”
Section: Resultsmentioning
confidence: 99%
“…18 Finally the interaction of fluorine with silicon interstitials has been widely proposed as a mechanism of suppressing boron transient enhanced diffusion. 2, [4][5][6][7][8][9][10]18 In this paper, experiments are performed to investigate how the fluorine implantation dose influences the thermal diffusion of boron marker layers in silicon. Boron secondary ion mass spectroscopy (SIMS) profiles are studied for different fluorine implantation doses and compared with the corresponding fluorine profiles.…”
Section: Introductionmentioning
confidence: 99%
“…22 Work on the effects of fluorine from a BF 2 + implant showed that shallower junctions could be obtained when BF 2 + was implanted instead of B + . 1,7,8 In later work 2-6,9-15,17,18 fluorine was implanted separately to the boron to characterize the effect of the fluorine on boron diffusion. This work showed that the fluorine implant reduced boron transient enhanced diffusion [2][3][4][5]9,11,13,14,[16][17][18] and increased boron activity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations